Numerical and Experimental Validation of the Applicability of Active‐DTS Experiments to Estimate Thermal Conductivity and Groundwater Flux in Porous Media. Issue 1 (12th January 2021) - Simon, N.; Bour, O.; Lavenant, N.; Porel, G.; Nauleau, B.; Pouladi, B.; Longuevergne, L.; Crave, A.
Abstract: Groundwater flow depends on the heterogeneity of hydraulic properties whose field characterization is challenging. Recently developed active‐Distributed Temperature Sensing (DTS) experiments offer the possibility to directly measure groundwater fluxes resulting from heterogeneous flow fields. Here, based on fundamental principles and numerical simulations, two interpretation methods of active‐DTS experiments are proposed to estimate both the porous media thermal conductivities and the groundwater fluxes in sediments. These methods rely on the interpretation of the temperature increase measured along a single heated fiber‐optic (FO) cable and consider heat transfer processes occurring both through the FO cable itself and through the porous media. The first method relies on the Moving Instantaneous Line Source model that reproduces the temperature increase and provides estimates of thermal conductivity and groundwater flux as well as an evaluation of the temperature rise due to the FO cable. The second method, based on the graphical identification of three characteristic times, provides complementary estimates of flux, fully independent of the effect of the FO cable. Sandbox experiments provide an experimental validation of the interpretation methods, demonstrate the excellent accuracy of groundwater flux estimates (<5%), and highlight the complementarity of both methods. Active‐DTS experiments allow investigating groundwater fluxes over a large range spanning 1 × 10 −6 −5 × 10 −2  m/s, depending on the duration of the experiment. Considering the applicability of active‐DTS experiments in different contexts, we propose a general experimental framework for the application of both interpretation methods in the field, making active‐DTS field experiments especially promising for many subsurface applications. Key Points: Numerical and experimental validation of two methods to interpret active‐Distributed Temperature Sensing (DTS) experiments in sediments Determination of thermal conductivity and groundwater flux with low uncertainties Definition of the applicability, range of measurements, and limits of active‐DTS experiments